Fast SR beam position and intensity monitor for the experiments to study fast-flowing processes - Aulchenko, V. M.; Glushak, A. A.; Kornievsky, M. A.; Shekhtman, L. I.; Tolbanov, O. P.; Tyazhev, A. V.; Zarubin, A. N. (Russian physics journal, 2025)
A Fast Processes station is proposed for studying the detonation and shock wave processes as part of the experimental stations at the SKIF Center for Shared Use. The station includes a number of DIMEX detectors (Detector IMaging EXplosions). A DIMEX is capable of detecting synchrotron radiation (SR) from each electron bunch in the storage ring. Since the bunches can deviate from the equilibrium orbit and differ in current, a fast monitor of the SR beam position and intensity is needed to increase the accuracy of signal magnitude measurements and to measure the relative position and power of the beam radiation from each electron bunch in the storage ring. The readings from this monitor would allow correcting the measurements of the DIMEX detectors. As part of the fast SR beam position monitor, it is planned to place 4 sensors to measure the signal in the vicinity of the beam on the top, bottom, right and left. The signal ratios in the corresponding pairs of sensors are supposed to change with the beam position, and the sum of the signals from all sensors will change with the change of the total SR flux. During the experiment, the beam monitor will record the signals from all sensors synchronously with the DIMEX detector. After the experiment, the results recorded from the DIMEX detector will be adjusted in accordance with the monitor sensor signals.